Electroporation facilitates introduction of reporter transgenes and virions into schistosome eggs. - Kristine J Kines; Gabriel Rinaldi; Tunika I Okatcha; Maria E Morales; Victoria H Mann; Jose F Tort; Paul J Brindley (Public Library of Science (PLoS), 2010)
The schistosome egg represents an attractive developmental stage at which to target transgenes because of the high ratio of germ to somatic cells, because the transgene might be propagated and amplified by infecting snails with the miracidia hatched from treated eggs, and because eggs can be readily obtained from experimentally infected rodents.We investigated the utility of square wave electroporation to deliver transgenes and other macromolecules including fluorescent (Cy3) short interference (si) RNA molecules, messenger RNAs, and virions into eggs of Schistosoma mansoni. First, eggs were incubated in Cy3-labeled siRNA with and without square wave electroporation. Cy3-signals were detected by fluorescence microscopy in eggs and miracidia hatched from treated eggs. Second, electroporation was employed to introduce mRNA encoding firefly luciferase into eggs. Luciferase activity was detected three hours later, whereas luciferase was not evident in eggs soaked in the mRNA. Third, schistosome eggs were exposed to Moloney murine leukemia virus virions (MLV) pseudotyped with vesicular stomatitis virus glycoprotein (VSVG). Proviral transgenes were detected by PCR in genomic DNA from miracidia hatched from virion-exposed eggs, indicating the presence of transgenes in larval schistosomes that had been either soaked or electroporated. However, quantitative PCR (qPCR) analysis determined that electroporation of virions resulted in 2-3 times as many copies of provirus in these schistosomes compared to soaking alone. In addition, relative qPCR indicated a copy number for the proviral luciferase transgene of approximately 20 copies for 100 copies of a representative single copy endogenous gene (encoding cathepsin D).Square wave electroporation facilitates introduction of transgenes into the schistosome egg. Electroporation was more effective for the transduction of eggs with pseudotyped MLV than simply soaking the eggs in virions. These findings underscore the potential of targeting the schistosome egg for germ line transgenesis.